HUBUNGAN TINGKAT PENDIDIKAN PENDIDIK PAUD DENGAN KETERAMPILAN MENGELOLA KELAS DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Maret, Selvina; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the relationship between the education level of PAUD educators and the skills in managing classes in the District of Tenayan Raya, Pekanbaru. This study is a correlation study consisting of independent variables (x), namely the level of teacher education and the dependent variable (y), namely the skills of managing the class. The population and sample in this study amounted to 101 PAUD educators in the Tenayan Raya District of Pekanbaru City. The instrument for collecting data is the relationship between the level of education of the teacher and the skills in managing the class using a questionnaire (questionnaire). The data collection technique in this study was using a scale. All questions are set or the questionnaire is presented in the form of a Likert scale consisting of five answer choices, namely: always (SL), often (SR), sometimes (KD), rarely (JR), never (TP). As the item selection criteria based on total item correlation for the Likert scale the rix limit is most often used ≥ 80. If all the items that reach a minimum coefficient of 0.80 the power of reasoning is considered to be very strong, as for the results of the skill questionnaire reliability managing the class in Tenayan Raya District, Kota Pekanbaru amounting to 0.951 means that it is greater than 0.80, this indicates that the class management questionnaire instrument in Tenayan Raya Subdistrict, Pekanbaru City is reabel and is suitable for use in research. Obtained the percentage of high school education level of 54% in the medium category. D2 is 43% in the high category. D3 is 40% in the low category. S1 is 92% in the high category.Key Words: Education Level, Classroom Management Skills